Unstandardized Treatment of Electroencephalographic Status Epilepticus Does Not Improve Outcome of Comatose Patients after Cardiac Arrest - Hofmeijer, Jeannette; Tjepkema-Cloostermans, Marleen C.; Blans, Michiel J.; beishuizen, Albertus; van Putten, Michel J. (Frontiers in Neurology, 2014)
Objective Electroencephalographic status epilepticus occurs in 9-35% of comatose patients after cardiac arrest. Mortality is 90-100%. It is unclear whether (some) seizure patterns represent a condition in which anti-epileptic treatment may improve outcome, or severe ischemic damage, in which treatment is futile. We explored current treatment practice and its effect on patients’ outcome. Methods We retrospectively identified patients that were treated with anti-epileptic drugs from our prospective cohort study on the value of continuous EEG in comatose patients after cardiac arrest. Outcome at six months was dichotomized between “good” (CPC 1 or 2) and “poor” (CPC 3, 4, or 5). EEG analyses were done at 24 hours after cardiac arrest and during anti-epileptic treatment. Unequivocal seizures and generalized periodic discharges during more than 30 minutes were classified as status epilepticus. Results Thirty-one (22%) out of 139 patients were treated with anti-epileptic drugs (phenytoin, levetiracetam, valproate, clonazepam, propofol, midazolam), of whom 24 had status epilepticus. Dosages were moderate, barbiturates were not used, medication induced burst-suppression not achieved, and treatment improved electroencephalographic status epilepticus patterns temporarily (< six hours). Twenty-three patients treated for status epilepticus (96%) died. In patients with status epilepticus at 24 hours, there was no difference in outcome between those treated with and without anti-epileptic drugs. Conclusions In comatose patients after cardiac arrest complicated by electroencephalographic status epilepticus, current practice includes unstandardized, moderate treatment with anti-epileptic drugs. Although widely used, this does probably not improve patients’ outcome. A randomized controlled trial to estimate the effect of standardized, aggressive treatment, directed at complete suppression of epileptiform activity during at least 24 hours, is needed and in preparation.